Resolving conflict of law issues in parental child abduction: Mediation as an effective mechanism - Che Soh @ Yusoff, Roslina; Abdul Hak, Nora; Hamid, Abdul Ghafur@Khin Maung Sein; Mohd Zin, Najibah; Mohamed Jani, Hidayati (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Abduction often involves the parents of the child. After a marriage is dissolved most parents will fight to have custody of the children. The party that is unable to lawfully obtain custody of children sometimes resort to abduction. Abduction of children is an issue that raises concern due to its effect on the child. Abducted children are sometimes even taken outside the country of abduction to another country by the non-custodian parent in order to prevent tracing and punishment. These attributes of abduction have a far reaching negative consequence on the child. The sudden separation of the child with his environment and the attempt to hide the child negatively affects the child physically and psychologically. The paper examines the position of parental child abduction under the Malaysian law and the approach of the courts in dealing with the matter. The paper also briefly discusses the position of child abduction under the international law and shariah and suggests mediation as an effective means to resolve the disputes involving parental child abduction. Doctrinal methodology is used in the paper in arriving at the findings of the work